DETERMINANTS OF INVESTMENT, LABOR MARKET ON ECONOMIC GROWTH IN MEDAN CITY - Gamot Malau, Albert; Hotman, Jan; Gunawan, April (Dinasti International Journal of Management Science, 2021)
One of the indicators of economic growth in a country is that the income in a country has increased. Economic growth can be calculated from real national income. Economic Growth Medan City is one of the cities that has a fairly high level of economic growth. So this study aims to analyze the determinants of investment, interest rates, labor on economic growth in the city of Medan. The results obtained from this study are (1) the Gross Regional Domestic Product of Medan City is positively related to all explanatory variables, namely the Medan City workforce and Medan City's Gross Regional Domestic Product last year (PDRBt-1). All signs of the alleged parameters are in line with expectations, the variable that has a significant effect is the Regional Domestic Product of Medan City last year. The estimation results show that an increase in the number of Medan City workers by 10 units will encourage an increase in Gross Regional Domestic Product by 99 units per year, (2) Medan City Household Consumption is positively related to all explanatory variables namely Consumer Price Index, Gross Regional Domestic Product Medan City, Export Value and Household Consumption of Medan City last year (PRKTt-1). All signs of the estimated parameters are in line with expectations, the variables that have a significant effect are the Consumer Price Index and the Regional Domestic Product of Medan City. The estimation results show that if the Medan City Consumer Price Index is increased by 10 units, it will encourage Medan City Household Consumption by 10 units.